Constructivist-Based Educational Games for Developing Social and Learning Skills of Children with Attention Deficit Hyperactivity Disorder: Permainan Edukatif Berbasis Konstruktivisme untuk Mengembangkan Keterampilan Sosial dan Belajar Anak dengan Gangguan Pemusatan Perhatian dan Hiperaktivitas - Nurhayati, Nurhayati; Mahabbati, Aini (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Inclusive early childhood education emphasizes equal learning opportunities and holistic child development. Specific background: Children with Attention Deficit Hyperactivity Disorder often experience barriers in maintaining focus and engaging in positive social interaction within group learning. Knowledge gap: Few studies have systematically applied constructivist-based educational games to address both social and concentration difficulties in early learners with this condition. Aims: This study examines how constructivist-oriented educational games can develop social interaction skills and learning concentration among kindergarten children with Attention Deficit Hyperactivity Disorder. Results: Implemented through two cycles of classroom action research, the study demonstrated significant progress—social interaction improved from 40% to 91.66%, and learning concentration from 39% to 85.71%. Novelty: The study presents an innovative application of constructivist pedagogy through play-based activities that nurture collaboration, emotional regulation, and sustained focus. Implications: Findings reinforce the importance of playful, inclusive, and child-centered approaches in supporting social and cognitive development in children with attention and behavioral challenges. Highlights: Constructivist-based educational play improved focus, emotional control, and collaboration in children with attention challenges. Significant development occurred in both social interaction and concentration across two research cycles. Playful learning created an engaging and supportive environment for inclusive early education. Keywords: Attention Deficit Hyperactivity Disorder, Constructivist Approach, Educational Games, Social Interaction, Learning Concentration